Writing with Blood: The Transformative Pedagogy of Teaching Students to Write Manifestos - Fahs, Breanne (Radical Teacher, 2019)
Given that manifestos are an understudied genre of writing, few undergraduate students learn about their history, style, and potential political impact.  This essay reviews the history of manifestos, followed by descriptions of teaching students to write their own manifesto in an upper-division women and gender studies course I teach on radical writings.  The rewards and possibilities of manifesto writing, alongside the hazards of teaching manifesto writing in a formalized institutional setting like academia, are explored.